MENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS IX.1 SMP N 1 KINALI - Zulhijrati, Zulhijrati (STKIP Pesisir Selatan, 2017)
Based on the observations that researchers have done in SMPN 1 Kinali can be concluded the low learning outcomes caused by the students less effective learning model used by teachers in the learning process. For that researcher as eye teacher of Math Lesson do research about Jigsaw type cooperative learning model to result of learning. This research is a Classroom Action Research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 23 students. Research data was collected using obeservation sheets. Data were analyzed using percentages. Based on the results of analysis of research data that has been presented for two cycles and the results of all the discussion, it can be concluded that Jigsaw type cooperative learning model can improve the quality of learning Mathematics and Jigsaw type cooperative learning model has a positive impact in improving student learning outcomes are characterized by increased learning mastery students in each cycle, that is cycle I (68.18%), and cycle II (90.91%)